The status of river water quality in some rural areas, in state of Johor and its effects to life - Shafii, Haryati; Miskam, Nurasyikin; Md. Yassin, Azlina; Shareh Musa, Sharifah Meryam (Malay Arts, Culture and Civilization Research Centre, 2018)
Water is a basic requirement of human and other life. Water resources stems from rivers, streams, drains, ponds and so forth. The river is the natural water resources are very important for a human habitat. Malaysian water quality assessment is determined by the water quality Index (IKA) issued by the Department of environment (DOE) based on class I, II, III and IV. Now a water pollution also occurs in rural areas has affected the water quality and marine life. The objective of this writing is to determine river water quality in rural areas based on IKA. Kajian telah dijalankan di beberapa batang sungai di kawasan luar bandar di negeri Johor bermula dari bulan Februari sehingga April 2015. Water quality sampling was done three times in four different study locations. Determination of water quality involves measurement parameters pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal nitrogen (AN) and suspended solids (SS). The Measurements are made IKA the total calculated and used to classify the river either as untainted, slightly polluted moderately polluted, contaminated and polluted. The study found the status of three rivers polluted level contaminated (class IV) and a river are classified at the level of medium-polluted (class III). Deterioration of the status of IKA for all rivers surveyed not only affects marine life, even limiting water use to humans, for example, to daily activities.